2010
DOI: 10.1039/b924330e
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced reduction and heat-induced oxidation of silver in transparent RSiO3/2 and RSiO3/2–TiO2 films

Abstract: Photoinduced reduction, resulting in nanoparticle formation, and heat-induced oxidation of doped silver have been demonstrated in silsesquioxane (RSiO(3/2)) and RSiO(3/2)-TiO(2) films (R = methyl, vinyl, and glycidoxypropyl) synthesized via the sol-gel method. The occurrence of redox behavior in the doped silver, i.e. formation and dissociation of silver nanoparticles (AgNPs) in the films, was confirmed by UV-Vis spectroscopy, IR spectroscopy, X-ray diffraction and transmission electron microscopy. The films c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…For instance, Ag-doped vinyl-silsesquioxane (ViSiO 3/2 )-TiO 2 films were synthesized by the following procedure [18]. ViSi(OC 2 H 5 ) 3 (Vi: vinyl group) in ethanol was partially hydrolyzed by mixing with AgNO 3 and HNO 3 .…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Ag-doped vinyl-silsesquioxane (ViSiO 3/2 )-TiO 2 films were synthesized by the following procedure [18]. ViSi(OC 2 H 5 ) 3 (Vi: vinyl group) in ethanol was partially hydrolyzed by mixing with AgNO 3 and HNO 3 .…”
Section: Synthesismentioning
confidence: 99%
“…UV-Vis and b IR spectra of Ag-doped ViSiO 3/2 -TiO 2 films before and after UV radiation for 10 min (230-440 nm, 50 mW cm -2 at 365 nm); c shows changes in absorbance at 420 nm of the film experienced repeated UV radiation for 10 min and heat treatment in air at 100°C for 1 h. Reproduced with permission from[18]. Copyright 2010 The Royal Society of Chemistry…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Ag + ion-doped films, in fact, showed sufficient homogeneity, reversibility, and durability for the practical use as holographic materials. 7) Sensitivity to visible light was further given to the films by bromination of Ag + ions, whereas the homogeneity and reversibility were deteriorated. 8) In this work, we found that the change of the halogen element from Br to Cl was very effective to improve reactivity upon visible light irradiation.…”
Section: )mentioning
confidence: 99%
“…89) Application of micropatterning technique to hologram formation has also been reported. 90)95) The basic concept is to fabricate sub-micropatterns in recording media, which contain TiO 2 . Reversible hologram formation was demonstrated in AgCl nanoparticle-doped RSiO 3/2 TiO 2 films (R: glycidoxypropyl organic functional group) by visible light irradiation and heat treatment (Fig.…”
Section: Micropatterningmentioning
confidence: 99%